PENGEMBANGAN E-MODUL MATA PELAJARAN PEKERJAAN DASAR TEKNIK OTOMOTIF SMK MUHAMMADIYAH IMOGIRI - wakhid subagyo (JURNAL VOKASI DEWANTARA (JVD), 2023)
The purpose of this research is to increase the effectiveness of learning, both in terms of time, funds, facilities, and manpower in order to achieve a goal optimally, and facilitate the learning process. This research is a development research. Development of E-learning module which refers to the development model of S.Thigharajan, Doroth Semmel.this research has four methods, namely the first introduction, the second development, the third research study and the fourth dissemination Based on the learning module for Basic Automotive Engineering subjects that have been validated by one material expert and one media expert, a trial was conducted on 28 students of class X of the Automotive Light Vehicle Engineering Department at SMK Muhammadiyah Imogiri. Based on the results of the analysis of this study, it shows that E-learning can produce good quality, and can be used as a source of learning materials. The results of this study can be proven by the average total score from the assessment of material experts with a total score of 3.48 out of a maximum score of 4 so that it can be said to be in the very feasible category and the average total score from the media expert's assessment is 3.40 of the score. a maximum of 4 so that it can be said to be in the very feasible category, the average score from the field test is 3.13 out of a maximum score of 4 so it can be said to be in the feasible category, so that the overall average results of the evaluation of material experts, media experts, and field test results get an average score of 3.28 out of a maximum score of 4 so that it is included in the appropriate category for use.